EFFECT OF DIETARY FERMENTED LAMTORO (Leucaena leucocephala) LEAVES FLOUR IN FEED ON DIGESTIBILITY AND HEMATOLOGICAL PARAMETERS OF CATFISH (Clarias sp.) - Achmad Noerkhaerin Putra; Anngy Chahya Pradana; Deny Novriansyah; Mustahal Mustahal (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2019)
Leucaena leaves is a potential ingredient for raw material feed of catfish. The aim of this study is to evaluate the effects of dietary fermented leucaena leaf on digestibility and hematological parameters of catfish. Four treatments and 3 replicates, namely: A (reference feed 70% + leucaena leaves meal 30%), B (reference feed 70%+fermented leucaena leaves meal with A. niger 30%), C (reference feed 70%+fermented leucaena leaves meal with R. oligosporus 30%), and feed D (reference feed 70%+fermented leucaena leaves meal with S. cerevisiae 30%) were used in this study. The juvenile catfish (initial weight was 5,45±0,16 g) are randomly distributed into eighteen tanks with 40 fish per aquarium. Each diet is randomly assigned to the triplicate aquarium and fed to fish three times a day up to satiation for 4 weeks. The results showed that fermented leucaena leaves treatments were significantly higher (P<0.05) than that control in final weight and feed conversion rasio. Nutrients digestibility and final weight were significantly highest (P<0.05) in fermented leucaena leaves with A. niger compared to the other treatment. The value of protein digestibility was significantly highest (P<0.05) in fermented leucaena leaves with A. niger (76,04%), followed by fermented leucaena leaves S. cerevisiae with (69,71%), fermented leucaena leaves meal with R. oligosporus (68,24%), and control (65,18). Leucaena leaves had no effect on physiological processes in catfish, as shown by hematological parameter values that were within the normal range.